Family support, diabetes self-management behavior, and HbA1c levels in Manggarai Regency, East Nusa Tenggara - Susilo, Leonardus Reynald; Dewi, Fatwa Sari Tetra; Huriyati, Emy (BKM Public Health and Community Medicine, 2022)
Purpose: This study examines the correlation between family support and diabetes self-management with control of blood sugar levels (HbA1c). Methods: This study employs a sequential mixed-methods approach, combining quantitative analysis with a cross-sectional design and qualitative analysis with a phenomenological design. This research was conducted in clinics and health centers with prolanis groups in Manggarai Regency, East Nusa Tenggara. Results: The average score for diabetes self-management was 4,482 (minimum 0 – maximum 10) and was significantly correlated with the control of blood sugar levels. The dimension of food control in diabetes self-management has a significant relationship with blood sugar control. The average value of family support is 2,433 (minimum 1, maximum 4) and shows no significant correlation with blood sugar control. The emotional dimension of family support significantly correlates with the control of blood sugar levels. Conclusion: Enhancing diabetes self-management behavior can lead to improved blood sugar control in Prolanis participants. This improvement can be facilitated by families who can accompany Prolanis participants at home.